Tingkat Minat Siswa dalam Mengikuti Ekstrakurikuler Futsal di SMAN 1 Pagaden Subang - Muhamad Reza Nur Hakim; Bambang Ismaya; Irfan Zinat Achmad (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2022)
The purpose of this research is to find out how much students are interested in futsal extracurricular activities in SMA Negeri 1 Pagaden students. This type of research is descriptive research. The population of this study were students of SMA Negeri 1 Pagaden class who had the same age level, namely 14-17 years. Population and sampling is using a purposive technique with the characteristics of people who play futsal. Descriptive data analysis techniques with calculations in the questionnaire. Based on the results of the discriminatory analysis showed that the average student interest in playing futsal was in the low category. This can be seen in both internal and external factors of SMA Negeri 1 Pagaden students